Severe hypoglycemia: Is it important to take into account the albuminuria value? - Jorge Rico-Fontalvo; Rodrigo Daza-Arnedo; Jose Bohorquez-Rivero; Jose Restom-Arrieta (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2023)
The authors conclude that in patients with DM2, more advanced CKD was associated with greater insulin use, proposing different explanations of this relationship, however, we consider that in addition to these findings, within the study there are no patients using Dipeptidyl Peptidase-4 Inhibitors (DPP4i), probably by that time they were not being used yet. Therefore, patients with advanced CKD only had insulin as the only option, which explains a greater frequency of its use in this group of patients.